Assessment of Masseter Muscle Appearance and Thickness in Edentulous and Dentate Patients by Ultrasonography - KESER, GAYE; NAMDAR PEKİNER, FİLİZ MEDİHA (BENTHAM SCIENCE PUBL LTD, 2018)
Objectives: The purpose of the present study was to examine ultrasonographic appearances of Masseter Muscle (MM) in dentate and edentulous patients without Temporomandibular Disorder (TMD). Materials and Methods: The thickness of the MM in 25 dentate (mean age: 30,68 +/- 10,49) and 24 edentulous (mean age: 61,46 +/- 9,71) patients, who visited routine dental examination, was measured at rest and at maximum contraction bilaterally. Examinations were performed using an Aloka Prosound a6 (Hitachi Aloka Medical Systems, Tokyo, Japan) equipped with an 8 MHz-wide bandwidth linear active matrix transducer (ranging from 1 to 15 MHz). The visibility and width of the internal echogenic bands of the MM were also assessed and the muscle appearance was classified as I of III types. Type I, characterized by the clear visibility of the fine bands; Type II, thickening echogenicity of the bands; Type III, disappearance or reduction in a number of the bands. Results: MM thickness at rest and contraction in the dentate group were significantly higher than the edentulous group (p < 0.05). Type I was the most common echogenic type in both dentate (right: 16 (64%), left; 15 (60%)) and edentulous patients (right; 22 (91.7%), left; 18 (75%)). In a dentate group, type II was significantly higher than the edentulous group in both the right and left sides (p < 0.05; p < 0.01, respectively). Age and gender seemed to have no significant effect on the echogenic type (p > 0.05). Conclusion: There were significant differences in the thickness at rest and contraction between the dentate and edentulous groups. It was clarified that ultrasonographic features of the MM in dentate and edentulous patients were different.
Keywords: Ultrasonographic appearances; Masseter muscle; Dentate group; Edentulous patients; Echogenic type; Temporomandibular disorder; TEMPOROMANDIBULAR DISORDER; MASTICATORY PERFORMANCE; FACIAL MORPHOLOGY; FEATURES